Forest structural heterogeneity positively affects bird richness and acoustic diversity in a temperate, central European forest - Shaw, Taylor; Scherer-Lorenzen, Michael; Müller, Sandra (Frontiers in Ecology and Evolution, 2024)
IntroductionForests managed for timber production can also be managed for biodiversity conservation by retaining structures typical of old-growth forests, which provide heterogenous structures for forest-dwelling species, including birds. Ecoacoustic monitoring of forest birds is now a well-studied field, however the extent to which acoustic indices can reflect bird assemblage responses to stands of lower or higher structural heterogeneity is disputed. MethodIn this study, we acoustically surveyed 75 plots over two years in mature, previously managed forests and computed acoustic indices from the recordings. We first identified an acoustic index that significantly correlated with bird richness over more than one spring season. Next, we tested the response of bird richness to individual forest structural elements using linear regressions. We then repeated this analysis but combined the individual structural elements into one structural composition variable using an NMDS and gam smooth overlay, to compare the effect of individual forest structures versus overall forest heterogeneity on bird richness. We then repeated this analysis using our selected acoustic index, the Normalized Difference Soundscape Index (NDSI), to see if it followed the same patterns as bird richness in response to individual and collective forest structural elements.ResultsOur results showed that plots with high bird richness were also associated with high NDSI values, and high values of both variables occurred in plots with high structural heterogeneity (tree species richness, tree size variability, and snag height variability) and low amounts of standing and lying deadwood. DiscussionOur findings suggest that once an acoustic index can be identified as a robust correlate of bird richness, it can serve as a proxy for the response of birds to differences in forest structural heterogeneity within a managed forest context. It is therefore possible for forest managers interested in conserving or increasing bird richness in their production forests to identify a robust acoustic index to track the response of bird richness to management decisions over time.